2017
DOI: 10.1542/peds.2017-0999
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age and Outcomes in Critical Congenital Heart Disease

Abstract: Infants born with CCHD are at high risk of neonatal morbidity. Morbidity remains increased across all GA groups in comparison with infants born at 39 to 42 weeks. This substantial risk of neonatal morbidity is important to consider when caring for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 37 publications
3
56
1
1
Order By: Relevance
“…Different results were reported by Steure and coauthors. [20] Late preterm infants in our study were found to have more neonatal complications compared to full-term infants. Nearly 32.9% of LPT infants had clinical symptoms of respiratory distress, and the most common cause of it in LPs was RDS.…”
Section: Discussionmentioning
confidence: 47%
“…Different results were reported by Steure and coauthors. [20] Late preterm infants in our study were found to have more neonatal complications compared to full-term infants. Nearly 32.9% of LPT infants had clinical symptoms of respiratory distress, and the most common cause of it in LPs was RDS.…”
Section: Discussionmentioning
confidence: 47%
“…In contrast, SGA, AGA, LGA, and Z score for BW all report measures standardized for GA and sex, and as such are often used as surrogate markers for fetal growth. Increased mortality in LBW infants with CHD does not address the question of whether fetal growth—as measured by SGA/AGA/LGA or Z score for BW—impacts this outcome since the increased mortality rate in LBW infants is mainly driven by lower GA, and it is well known that GA is a major determinant of mortality in infants with7, 8, 25 and without CHD 26…”
Section: Discussionmentioning
confidence: 99%
“…However, more recently, early‐term infant vulnerability has been documented and several studies in infants without CCHD have shown that early‐term infants born at 37 to 38 weeks have a higher incidence of respiratory distress, developmental morbidities, and even infant mortality 32, 33. In infants with CCHD, 2 studies have shown increased mortality, neonatal morbidities, and postoperative complications in early‐term versus full‐term infants 7, 8. Our current study suggests that Z score for BW has the most granular effect in early‐term infants with CCHD, making this group particularly vulnerable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations